Hypertrophy of Ligamentum Flavum in Lumbar Spine Stenosis Is Associated with Increased miR-155 Level - Chen, Jianwei (Hindawi Publishing Corporation, 2014)
Hypertrophy of ligamentum flavum (LF) contributes to lumbar spinal stenosis (LSS) and is caused mainly by fibrosis. Recent data indicate that miR-155 plays a crucial role in the pathogenesis of different fibrotic diseases. This study aimed to test the hypothesis that miR-155 exerts effects on LF thickness by regulating collagen expression. We found that LF thickness and the expression of collagen I and, collagen III were higher in LF from LSS patients than in LF from lumbar disc herniation (LDH) patients (P < 0.01). The expression of miR-155 was significantly higher in LF from LSS group than in LF from LDH group (P < 0.01). miR-155 level was positively correlated with LF thickness (r = 0.958, P < 0.01), type I collagen level (r = 0.825, P < 0.01), and type III collagen level (r = 0.827, P < 0.01). miR-155 mimic increased mRNA and protein expression of collagen I and collagen III in fibroblasts isolated from LF, while miR-155 sponge decreased mRNA and protein expression of collagen I and III in fibroblasts. In conclusions, miR-155 is a fibrosis-associated miRNA and may play important role in the pathogenesis of LF hypertrophy.